The first description of the male Euophrys atrata and E. bulbus from southern China (Araneae: Salticidae) - Zha, Shanjie; Jin, Chi; Zhang, Feng (Zootaxa, 2014)
The males of Euophrys atrata Song & Chai,1992 and Euophrys bulbus Bao & Peng, 2002 are described and illustrated for the first time from southern China.